(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
On the other hand, some managers’ bank on highly sophisticated, technology based systems such as Flexible Manufacturing Systems (FMS), Com-puter Integrated Manufacturing Systems (CIMS), Information Systems (IS) that enable e-business through the use of software packages for Enterprise Resource Planning (ERP), Supply Chain Management (SCM), Customer Relationship Management (CRM) etc. But an intriguing question that has not been answered completely is ’how do managers make a decision of implementing a ’management based and people oriented philosophy and practice’ (say LMS) or a technically sophisticated system (say CIMS)?’ Implementing such massive change management programmes require a strong justification for the managers to convince the top management, as it involves huge investment and creates a longstanding impact on various resources. But such justification problems are quite complex. Traditional techniques cannot be applied as they do not ac-count for intangible factors and benefits offered, which necessitate the use of Multi-Criteria Decision-Making (MCDM) models. Hence in this paper, an attempt has been made to demonstrate the application of a MCDM model, namely, the Performance Value Analysis (PVA) to analyse the alternatives (i.e., change management programmes) based on its impact on various performance measures of an organisation. A detailed algorithm of the PVA model is demonstrated using a case situation, which showed that LMS is the best for the given situation, as it results in overall improvement in the performance of the organization.